“Somos libres, seámoslo siempre”. Sobre la música en tiempos de la independencia del Perú: Entrevista al doctor Eduardo Torres Arancivia - de Belaunde, Carolina (Notas de Antropología de las Américas, 2023)
The lyrics of the Peruvian national anthem —written by José de la Torre Ugarte andmusicalized by José Bernardo Alzedo in 1821— sing to freedom, equality, happinessand unity. “We are free, let us always be” are words that we need to remember andreaffirm frequently, especially during times of social and political turmoil. Approachingthe bicentennial of the independence of the country, we interviewed HistorianEduardo Torres Arancivia about the music that accompanied the first years of thenovel republic. With his characteristic rigor, Torres Arancibia offers us a valuablecontribution on a little-studied subject: the context, the emotional power and theimportance that music had within the promise of nation-building in Peru.